2020
DOI: 10.1016/j.isci.2020.101681
|View full text |Cite|
|
Sign up to set email alerts
|

Generating Multibillion Chemical Space of Readily Accessible Screening Compounds

Abstract: Summary An approach to the generation of ultra-large chemical libraries of readily accessible (“REAL”) compounds is described. The strategy is based on the use of two- or three-step three-component reaction sequences and available starting materials with pre-validated chemical reactivity. After the preliminary parallel experiments, the methods with at least ∼80% synthesis success rate (such as acylation – deprotection – acylation of monoprotected diamines or amide formation – click reaction with fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
139
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(139 citation statements)
references
References 31 publications
0
139
0
Order By: Relevance
“…Make-on-demand chemical libraries will soon exceed the 100 billion threshold [1][2][3] , while structure-based virtual screening (SBVS) is well projected to remain the gold standard method for early-stage drug discovery. Molecular docking implemented on high-performing computational resources has already been proven successful in identifying potent ligands from extensive databases (from 100s of millions to up to 1 billion chemicals) for several targets [4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…Make-on-demand chemical libraries will soon exceed the 100 billion threshold [1][2][3] , while structure-based virtual screening (SBVS) is well projected to remain the gold standard method for early-stage drug discovery. Molecular docking implemented on high-performing computational resources has already been proven successful in identifying potent ligands from extensive databases (from 100s of millions to up to 1 billion chemicals) for several targets [4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to that, the library members 4 bearing a Boc-protected amino function were deprotected in silico to give 74,093 functionalized macrocycles 6 suitable for further "post-pairing" modification at the amino group. Taking into account our previous experience with REadily AccessibLe (REAL) Space methodology, [51] a chemical space of at least billion (10 9 ) macrocycles can be reached with such modifications.…”
Section: Resultsmentioning
confidence: 99%
“…The "couple" phase was performed according to a convenient modified one-pot protocol that was used by us for similar three-step reaction sequences previously. [51] It was found that 323 out of 383 experiments were successful for the preparation of dienes 5 (84 % synthesis success rate, 45 % average yield). 22 library members 5 were obtained in less than 10 mg amount and were discarded for the next step.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations